2007
DOI: 10.1007/s11418-007-0216-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of some medicinal plant extracts

Abstract: Antibacterial activity of hot aqueous and methanolic extracts prepared from six plants (Terminallia chebula, Terminallia bellerica, Phyllanthus emblica, Punica granatum, Lawsonia alba and Mikania micrantha) used in traditional folk medicines of India were screened against five pathogenic bacteria (Staphylococcus aureus MTCC 2940, Bacillus subtilis MTCC 441, Escherichia coli MTCC 739, Proteus vulgaris MTCC 426 and Enterobacter aerogenes MTCC 111). The highest antibacterial potentiality was exhibited by the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 8 publications
3
66
0
1
Order By: Relevance
“…Although a significant number of studies have been used to obtain purified phytochemicals, a very few screening programmes have been initiated on crude plant materials. It has also been widely observed and accepted that the medicinal value of plants lies in the bioactive phytocomponents present in the plants [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . The results of the present study are encouraging as all the tested extracts revealed antibacterial potential, although the inhibitory activity was strain specific and concentration dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Although a significant number of studies have been used to obtain purified phytochemicals, a very few screening programmes have been initiated on crude plant materials. It has also been widely observed and accepted that the medicinal value of plants lies in the bioactive phytocomponents present in the plants [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . The results of the present study are encouraging as all the tested extracts revealed antibacterial potential, although the inhibitory activity was strain specific and concentration dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Among the seven bacteria, this extract produced greatest inhibition against S. paratyphi and S. typhi. Literature revealed that, herbal products from the natural resources represent a promising source of antimicrobial agents for the reason that they are natural and affordable, particularly for rural communities (Ghosh et al, 2008). Approval of medicines from herbal sources as another form of medical care is increasing since they are serving as sources of novel antibiotic prototypes.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour suppressor genes are under expressed in cancer cells while, oncogenes are over expressed 23 . Summarizes the main oncogenes and tumour suppressor genes and their role in cancer development.…”
Section: Fig 1: the Mechanism On Cancer Therapymentioning
confidence: 99%